Head and neck squamous cell carcinoma in the young: a spectrum or a distinct group? Part 1. - Toner, Mary; O'Regan, Esther; Sheils, Orla (My University, 2009)
While most head and neck squamous carcinoma (HNSCC) occurs in older people, an increasing number of young patients are being affected worldwide, with up to 5.5% <40. These are predominantly oral and oropharyngeal cancers. Some patients have heavy exposure to the usual risk factors, but an increasing number do not. Part of this trend appears to be due to rising numbers of HPV associated tonsil carcinoma, particularly in males (smokers and non-smokers). A subset of young patients, however, is non-smoking females usually with tongue cancers, not related to HPV, the aetiology of which is unclear. Various mechanisms may be at work here: the variation in ability to detoxify the products of smoke and alcohol varies in individuals, which may explain why environmental exposure to smoke seems to play a role in some non-smokers with HNSCC. The role of marijuana remains possible but uncertain, and it may be that anaemia is a co-factor. There is an increased risk of HNSCC in first degree relatives of HNSCC patients, and while inherited syndromes associated with HNSCC are rare, elucidation of their genetics may help to develop our understanding the disease in these young patients without recognised risk factors.
PUBLISHED
Keywords: Oncology; head and neck squamous cell carcinoma (HNSCC); Cancer